Pablo Picasso Dando Instrucciones a Una Modelo en Su Taller de Pintura - Unknown author (NC, 2026)
Pablo Picasso giving instructions to a model in his painting workshop. Unknown author. Date: Circa 1955.
Droits : Licence indiquee par Wikimedia Commons
Keywords: peinture; peintres; artistes peintres; picasso; photo; archives photographiques; photographie; Art